Working Through and Around: Exploring Rural Public Health Nursing Practices and Policies To Promote Rural Women's Health - Beverly D Leipert; Sandra Regan; Robyn Plunkett (Rural Nurse Organization; Binghamton University, 2015)
Purpose: To discuss findings from research in Ontario, Canada, that addresses the following objectives: 1) identify organizational attributes and local and provincial health policies that enable or impede the work of Ontario public health nurses to improve rural women's health, and 2) critically examine roles, job descriptions, and practices of Ontario PHNs that will improve rural women's health. Sample: 20 frontline PHNs and 14 supervisors and managers in three Ontario public health units that serve people who live in rural locations. Method: Six focus group interviews were conducted with PHNs and PHN managers in three rural Ontario public health units. Study participants were asked to describe policies and practices that guided their practice regarding rural women's health, identify organizational attributes that enable or impede public health nursing practice regarding rural women's health, and indicate roles and practices for PHNs to improve rural women's health. Findings: 1) Policies address rural women's health and rural public health minimally or not at all, 2) PHN practice is primarily focused on child bearing women and children to the exclusion of other populations of rural women such as seniors, 3) PHNs work through and around policies to address rural women' s health more effectively, and 4) institutional, government, community, professional, and personal factors play significant roles in shaping public health nursing practice and policy regarding rural women's health. Conclusions: This research facilitates understanding regarding policies, contexts, and values that shape rural PHN practice, and provides evidence for policies and practices that enhance and support public health nursing for more effective promotion of rural women's health. Clearly, more investigation is needed; this research forms the basis for ongoing inquiry in this area. Keywords: rural public health nursing, rural women's health, policy, practice, Canada DOI:  http://dx.doi.org/10.14574/ojrnhc.v15i1.342